Ventilatory performance of AMBU® AuraGain™ and LMA® Supreme™ in laparoscopic surgery: A randomised controlled trial. Issue 5 (September 2021) - Zhang, Jinbin; Drakeford, Paul A; Ng, Vicky; Seng, Zhiquan; Chua, Maureen; Tan, Norman; Mathew, David; Teoh, Wendy H
: The Ambu® AuraGain™ (Ambu A/S, Ballerup, Denmark) is a newer phthalate-free, single-use supraglottic device with the advantage of a facility for tracheal intubation if necessary intraoperatively. We compared the oropharyngeal leak pressures and other performance variables between the AMBU AuraGain and the LMA® Supreme™ (Teleflex Medical, Athlone, Co. Westmeath, Ireland) in patients undergoing laparoscopic cholecystectomy and preperitoneoscopic inguinal herniorrhaphy with carbon dioxide insufflation under controlled ventilation. We recruited 120 American Society of Anesthesiologists physical status class I–3 patients between the ages of 21 and 80 years undergoing laparoscopic cholecystectomy or preperitoneoscopic inguinal herniorrhaphy into this single-centre randomised controlled trial. The primary outcome measure was the oropharyngeal leak pressures. Secondary outcomes included insertion parameters, ventilatory characteristics and postoperative sequelae. The AuraGain had slightly but significantly higher oropharyngeal leak pressures than the LMA Supreme (mean (standard deviation) 26.1 (6.9) versus 21.4( 4.7) cmH2 O, P  < 0.010). The overall insertion success of the AuraGain was comparable to the LMA Supreme (AuraGain 58/60 (96.7%); LMA Supreme 56/59 (94.9%), P  = 0.679). The AuraGain was deemed more difficult to insert than the LMA Supreme, with 26/60 (43.3%) of AuraGain insertions graded easy versus 48/59 (81.4%) of LMA Supreme, P  < 0.001. The mean time to insertion of the AuraGain was slightly longer than the LMA Supreme, 32.2 (10.5) versus 28.3 (12.0) s, P  < 0.001. Intraoperative device failure occurred following carbon dioxide insufflation in one AuraGain and three LMA Supremes, bringing the perioperative success rate of AuraGain and LMA Supreme to 95% and 89.8%, respectively, P  = 0.322. No cases of regurgitation and aspiration occurred, and minor postoperative complications were similar. The AuraGain exhibited higher oropharyngeal leak pressures than the LMA Supreme, but was slightly more difficult to insert. The higher oropharyngeal leak pressures suggest that ventilation might be less affected by high peak inspiratory pressures when using the AuraGain than the LMA Supreme.